Soberania alimentar e o assentamento Mulungu no semiárido cearense - Pereira, Simone Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The starting point of this study is the need for change in the agrarian structure of the country. Land concentration has led many people to suffering and misery, thus causing tensions and conflicts. The objective of this paper is to present the strategies of building food sovereignty from the conception of organized peasants, having as territory of research the Mulungú Settlement, located in the state of Ceará, observing the way they guarantee the production, access and consumption of food. Our field of study goes beyond the settlement and the peasants to also address the relationship of peasants organized with society, because this agrifood management is wrapped in a dimension that is crucial and determines the culture and identity of the people. We also approached what La Via Campesina International is thinking regarding the internationalization of the struggle of the peasants in a non-hegemonic perspective. The theoretical study, field research and the systematization of research point to the need of a globalization food sovereignty policy, which means the implementation of public policies that value local production of healthy and sufficient food for good nutrition of the population, and an agricultural sector that contributes to the generation of employment, housing, land, water and clean and free air for everyone. In these frameworks, the research examines a case of attempt to build policies for food sovereignty, from the organization of workers in the semiarid region of Ceará and the forms, limits and challenges to the peasant organizations with regard to the organization of labor for healthy food production in adverse conditions and against agribusiness

O ponto de partida deste estudo é a necessidade de mudança na estrutura agraria do país. A concentração de terras tem levado a muitas pessoas ao sofrimento e miséria, provocando assim tencionamentos e conflitos. No século XXI, a consolidação do projeto hegemonico do capitalismo no campo, caracterizado como agronegócio, se contrapõe totalmente ao que as organizações de camponeses se propoem, tanto do ponto de vista da sua relação com a terra como tambem os meios de produção de alimentos. A problematica da produção de alimentos poluídos pelo uso de agrotóxicos, da fome e da falta de moradia e trabalho digno têm se colocado como um grande desafio na nossa sociedade. Desta forma a Via Campesina Internacional tem se proposto a pensar a internacionalização da luta dos camponeses numa perspectiva contra hegemonica. Uma proposta de solução central da Via, analisada nesta dissertação, é a universalização de uma política de soberania alimentar, quer dizer, a implementação de políticas públicas que valorizam a produção local de alimentos saudáveis e suficientes para a boa nutrição da população, bem como um setor agrícola capaz de contribuir na geração de trabalho, moradia, terra, água e ar limpo e livre para todos e todas. Neste marco essa pesquisa examina um caso de tentativa de construção das políticas de Soberania Alimentar num assentamento Mulungú no Semiárido Cearense, onde uma organização da Via, o Movimento dos Trabalhadores Rurais Sem Terra (MST), tem feito um esforço durante os últimos anos para por em prática a estratégia. Vamos assim analisar as formas, limites e desafios para essa construção de fato
Keywords: Geografia; Reforma agraria - Brasil; Alimentos; Assentamentos humanos; Camponeses; Agroindústria; Geography